Vigorexia, an eating disorder in modern times (Research, Society and Development, 2021)
Objective: To investigate the relationship between vigorexia and body dissatisfaction, mental and eating disorders in adolescents, adults, weightlifters, gym regulars and bodybuilding athletes. Methodology: This is a literature review conducted from 2010 to 2020 based on data from the PubMed and Scielo platforms.Results: It was verified that 22 articles were included and 12 were excluded, totally evaluated based on the several factors that influence the development of muscular dysmorphia, such as the standard of beauty set by society and the media that propagate information and images of a perfect body.Final Considerations: As a result, it is essential to follow the signs shown by the patient and how to lead them to prioritize their physical and mental well-being so that appropriate intervention and adequate clinical-nutritional and psychological guidance can occur.